The effect of internal capabilities and external environment on small and medium sized enterprises’ international performance and the role of the foreign market scope : the case of Malaysian halal food industry - Ismail, Noor Azlin; Kuivalainen, Olli (2012)
Although the extant research suggests that e.g. knowledge-based capabilities are key determinants of the international performance of the SMEs, as they lack physical and financial resources, we still do not know enough about the factors which lead to their success. Furthermore, although there is international entrepreneurship (IE) research which originates from different backgrounds of industries and nations the bulk of the existing research has tended to focus on firms from developed countries and high technology industries and consequently the validity of the findings can be questionable within the Asian region, for example, as the early and rapid internationalization of Asian SME is influenced by local governments and cultural values. Some industries and their internationalization may be critically affected by these issues. In this paper we explore internationally operating SMEs and determinants of their international performance. First, we study the effects of a firm’s internal capabilities (such as international entrepreneurial orientation, foreign market experiential knowledge) on international performance, and second, we focus on the SMEs’ external environment such as globalization phenomenon, industry and domestic market conditions and local institutional factors which may have an effect on international performance. Third, we will explore the possible moderating role of the foreign market scope (as the outcome of the internationalization strategy) in these relationships. Although there are some exceptions it seems that multinationality or regional or global diversity of firms’ operations, which can be seen as core issues in the international management research, are often missing from IE studies. This paper extends our knowledge on this contextual issue by focusing on one emerging market, i.e. Malaysia, and halal food industry also from the developing country perspective. Building from past literature review and existing theories, this study investigates the relationship of small and medium enterprises’ (SMEs) specific internal capabilities, external environment and international performance in the Malaysian halal food industry holistically. The results show that foreign market knowledge is significant determinant of international performance in this context and this supports the classed stage models of internationalization. However, the findings reveal that the holistic models are of importance as both internal and external factors shape the performance. Furthermore, the findings reveal that geographical focus of the firms, i.e., foreign market scope level(measured by the number of regions a firm operates in) moderates the focal relationship. For SMEs operating in higher number of regions (global scope) showed a better international performance compared to those firms in lower number of scope (international scope).The results of this study shed light on the characteristics of these two types of firms. Future studies should focus more on geographical presence of the SMEs.